Analysis Of The Effect Of Economic Perceived Benefit And Social Interaction On Purchase Intention Mediated By Trust On Tokopedia - Rr Canthika Wahyu Safitri (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to examine the influence of Perceived economic benefits (PEB) and social interactions (SI) on consumer purchase intention by using consumer trust as a mediating variable. This study uses Tokopedia E-Commerce as an object with the aim of determining whether the economic and social perspectives of Tokopedia E-Commerce users are able to influence consumer purchasing intention. This study uses a quantitative approach involving 150 research respondents through a questionnaire method which is then tested statistically using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) tool. The findings of this study indicate that: 1) perceived economic benefits and social interactions have a positive and significant effect on consumer purchase intention and trust. 2) consumer trust is proven to be able to mediate the influence of perceptions of economic benefits and social interactions on consumer purchase intention, and 3) consumer trust has a positive effect on consumer purchase intention. The implication of these findings is that Tokopedia must focus on increasing economic benefits and social interactions to build consumer trust, which in turn will increase consumer purchase intention.